1985
DOI: 10.4039/ent1171445-11
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Two Pine Oils for Protecting Lodgepole Pine From Attack by Mountain Pine Beetle (Coleoptera: Scolytidae)

Abstract: Can. Ent. 117: 143-152 (1985) Residue analysis of apple foliage obtained from an orchard treated with the insecticides cypennethrin, fenvalerate, deltamethrin, permethrin, and azinphos-methyl revealed detectable residues on the leaves 8-9 weeks after the last treatment. Laboratory studies of foliage showed that of the synthetic pyrethroids, permethrin was initially as toxic as the other synthetic pyrethroids; however, its toxicity decreased considerably by the 5th and 6th week post-treatment. Azinphos-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our results on a dipteran species suggest that pine oil could modify the behavior of insects in a much more diverse taxonomic range than the forest coleopterans which have been the subject of previous research (Nijholt 1980;Nijholt et al 1981;Alfaro et al 1984;Richmond 1985). Although the DC,, of 0.1% is relatively high, Norpine-65 is a crude mixture.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our results on a dipteran species suggest that pine oil could modify the behavior of insects in a much more diverse taxonomic range than the forest coleopterans which have been the subject of previous research (Nijholt 1980;Nijholt et al 1981;Alfaro et al 1984;Richmond 1985). Although the DC,, of 0.1% is relatively high, Norpine-65 is a crude mixture.…”
Section: Discussionmentioning
confidence: 59%
“…Pine oil (Norpine-65, Northwest Petrochemicals, Anacortes, WA, USA) is a derivative of paper pulp waste from pulp mills, and is a complex mixture of varying amounts of monoterpenes and other natural products. It acts as a non-insecticidal repellent and antifeedant for ambrosia beetles, bark beetles, and conifer-infesting weevils (Nijholt 1980;Nijholt et al 1981;Alfaro et al 1984;Richmond 1985). Our objective was to test pine oil as an oviposition deterrent that could prevent or reduce oviposition by D. antiqua.…”
Section: Introductionmentioning
confidence: 99%
“…The close association of xylem resin of pines with the success or failure of bark beetle attack has been studied for a long time, starting with observations by A. D. Hopkins (1909), followed by early experimental work by Miller (1950), Callaham (1955), Vité and Wood (1961), and by experimental breeding and bioassay by Smith (1982b). Richmond (1985) showed that pine oil-a liquid aggregate of pine resin extracts with limonene as the primary constituentcould, when applied as a spray to the trunk, protect P. contorta from attack by the Dendroctonus ponderosae. One interesting and dramatic exception to the protective function is the very different role that resin plays in the operation of bark beetle pheromones.…”
Section: General Introductionmentioning
confidence: 99%
“…They did not mention phytotoxicity. Richmond (1985) sprayed lodgepole pines in Colorado to a height of 5 m with Norpine-and BBR-2 but did not report any phytotoxicity.…”
Section: Phytotoxicity Of Bbr-2mentioning
confidence: 99%